Impact of Education Program upon Nurses’ Knowledge towards Children under Mechanical Ventilation at Pediatric Teaching Hospitals in Baghdad City - abbas, Fatima; Mua’ala, Ekbal (Iraqi National Journal of Nursing Specialties, 2013)
Objective: impact of the education program for nurses’ knowledge toward children under mechanical ventilation, and to find out the relationships between nurses’ knowledge and their general information. Methodology: Quasi experimental study was carried out at the respiratory care units of Baghdad Pediatric Teaching Hospitals started from February15th, until September 26th, 2011, A purposive (nonprobability) sample of (23) nurses working in the respiratory care units, were selected from Children Welfare and Pediatric Central Teaching Hospitals. The data were gathered through using of the constructed multiple choice questionnaire using to evaluate the nurses knowledge using checklist, The questionnaire consists of two parts the first one is general information data and the second part is nurses’ knowledge multiple choice form used pre test before application of the program and post test after the application of the program. Descriptive statistical analysis procedure (frequency, and mean of score and standard deviation) and inferential analysis procedure (person correlation coefficient and ttest and ANOVA). Results: The findings of the study indicated that nurses have moderate knowledge in pre test. But post evaluation revealed high level of knowledge among nurses at RCU toward children under mechanical ventilation. The program reflects an effect on nurses’ knowledge. There were no statistical significant association between nurses’ knowledge and their general information. Recommendations: The study recommended that great focusing should be directed toward the educational aspects at respiratory care units by providing educational posters, guidelines, pamphlets and manuals to enhance nurses’ knowledge at RCU.